Estudio sobre la competitividad de la industria azucarera en Mexico - Francisco Campos-Ortiz; Mariana Oviedo-Pacheco (Banco de México, 2013)
– In this paper, we study various key structural features of sugarcane production and sugar mills in Mexico. Regarding the production of sugarcane: (a) we document a U-shaped relationship between the size of sugarcane cultivation plots and their yield, and show suggestive evidence that this relationship is driven by the more intensive use of inputs in smaller and larger plots relative to those of medium size; (b) we argue that there are factors that complicate the functioning of the land market; and (c) we present evidence refuting the conjecture that the mechanism used to determine payments for sugarcane affects negatively the quality of this crop. With respect to sugar mills, we find that those mills that are able to generate electricity more efficiently tend to observe higher returns in sugar production.
Keywords: D23; D24; L66; Q1; 330; Sugar; Sugar Industry; Competitiveness; Sugarcane; Plot Yield; Sugar Mill Efficiency